Collision avoidance system proposed by a model using NRF24L01 and infrared sensor - Khan, Salsabil (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.